The different faces of international posting: Why do companies use posting of workers?. (March 2022) - Lens, Dries; Mussche, Ninke; Marx, Ive
The importance of the posting of workers across EU borders has grown considerably in the past decade, causing concern regarding its impact on labour standards in Europe. This article asks why posting has taken such a flight. Building on quantitative analysis and in-depth interviews set against other sources, we shed light on employer motives for deploying posted workers. We develop a typology of posting which shows that while cost minimization is a crucial motive, especially in sectors where labour cost is an important competitive concern, a much wider set of motives are at play. Skill shortages across all levels of the skills spectrum play a crucial role in every sector. In addition, companies use sub-contracting for highly specialized temporary work as well as for routine tasks. Posting is also used for career development, especially of high potentials. Based on the wide array of employer motives for the use of posting, our typology distinguishes between 'competition posting', 'specialisation posting' and 'expert posting'. The article discusses some implications for EU policy vis-a-vis posted work.